2014
DOI: 10.5502/ijw.v4i1.1
|View full text |Cite
|
Sign up to set email alerts
|

Religion and wellbeing around the world: Social purpose, social time, or social insurance?

Abstract: Abstract:A number of studies find that religious people are happier than non-religious ones. Yet a number of fundamental questions about that relationship remain unanswered. A critical one is the direction of causality: does religion make people happier or are happier people more likely to have faith in something that is beyond their control? We posit that the relationship between religion and wellbeing is mediated by factors ranging from intrinsic purpose, to its social aspects, to its role as an insurance me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(46 citation statements)
references
References 81 publications
1
39
1
Order By: Relevance
“…However, his finding is not directly comparable to the current study since my measure of the affective domain is different from the one employed in his study, which used the single‐item self‐reported happiness measure in the General Social Survey. A recent study that used a similar measure to ours reports a finding that is more consistent with ours (Graham and Crown ), implying that how these different domains of subjective well‐being are measured can be important.…”
Section: Summary and Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…However, his finding is not directly comparable to the current study since my measure of the affective domain is different from the one employed in his study, which used the single‐item self‐reported happiness measure in the General Social Survey. A recent study that used a similar measure to ours reports a finding that is more consistent with ours (Graham and Crown ), implying that how these different domains of subjective well‐being are measured can be important.…”
Section: Summary and Discussionsupporting
confidence: 87%
“…This study also examines religion's relationship with both the cognitive and the affective domains of subjective well-being. With the exception of a few (e.g., Ellison 1991;Graham and Crown 2014), most previous studies on religion and subjective well-being have measured well-being with a single survey question on life satisfaction or general happiness. The former is considered to mostly reflect the cognitive domain; the latter arguably taps into the affective domain, but studies have shown that self-reported happiness also has a substantial cognitive component (Diener et al 2010) and often behaves similarly to measures of the cognitive domain (e.g., Putnam and Helliwell 2004).…”
Section: Religious Participation and Subjective Well-beingmentioning
confidence: 99%
See 2 more Smart Citations
“…Mental health includes seeing their children grow up and succeed, spirits of the Lao people who are happy in their occupation, living in the safe environment, having good leader and public management, proud and satisfied with their living, meriting and doing religion's activities. Especially for religion it is an important dimension of human experience which is positive relation with wellbeing (Graham & Crown, 2014).…”
Section: (Informant Interview 2012-2013)mentioning
confidence: 99%